Effective methods for software engineering - Summers, Boyd L. (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
"This book presents methods for analyzing software engineering problems, designing solutions, coding effectively, and testing software"--
" An Auerbach book"
OCLC-licensed vendor bibliographic record.
Keywords: Software engineering; COMPUTERS / Information Technology; COMPUTERS / Programming / Software Development; MATHEMATICS / General